Current Status and Overview of Farm Mechanization in Sudan - Devkota Wasti, Mina Kumari; Ahmed, ElRashid; Devkota, Krishna (2025)
The agricultural sector forms the backbone of Sudanese life and is a key driver of the national economy. In 2021, it provided employment and supported the livelihoods of 67% of the population, contributing 26% to the GDP and 30% to export earnings. Since Sudan's independence in 1956, the country’s agricultural policy has prioritized increasing crop production by adopting high-yielding varieties and improving crop management practices, including farm mechanization in both irrigated and rainfed systems. This policy received support from international organizations like the World Bank, aimed at securing food for the growing population. In 1964, the Sudanese government sought financial assistance for land clearance and the establishment of mechanized farms. By the early 1970s, large-scale agricultural schemes emphasizing mechanization were implemented. The establishment of the Mechanized Farming Corporation (MFC) encouraged both private and government entities to adopt mechanized farming, especially in Gedarif state, which became a hub for mechanized rainfed farming and a significant contributor to national food production. Sudan was ranked as one of the top countries in Africa with 24800 tractors of various sizes in 2008. The average number of tractors between 2009-2013 was 31770 and was further raised to 47686 tractors in 2019. As a result, the total land area served by a single 85- horsepower (hp) tractor decreased from 892 ha in 2014 to 602 ha in 2019. In addition, the number of seed drills and seeders nearly doubled between 2015 and 2019 mainly due to the expansion of area under grain crop cultivation, particularly wheat.